Pemikiran al-Syāfi‘ī Tentang Kurikulum Pendidikan - Rahmat Rifai Lubis (Sekolah Tinggi Agama Islam Sumatera Medan, 2015)
al-Imām al-Syāfi'ī is a scholar whose ideas almost always been a reference for all disciplines, including education. His thinking in the field of education, especially regarding the elements set forth the educational curriculum. According to the educational curriculum is not only limited to religious sciences course (naqliyah), but also on general knowledge (aqliyah). In addition, he is also a person skilled in designing the curriculum. His expertise in this case, can be used as a reference today by all those involved in education. Of course it is useful for the quality of education in the future